DAMPAK SOCIAL EXPECTATION AND PRODUCT SENSORIAL EXPERIENCE TERHADAP KEPUTUSAN PEMBELIAN PRIA DALAM PRODUK PERAWATAN WAJAH - Leo Alexander Tambunan (Business Management Journal, 2017)
Health care for skin is no longer women’s territory anymore. Nowadays, male care products market in the cleaning and skin care segments experiencing tremendous growth. On the basis of these, the authors are interested in studying the impact of male personal care product attributes against a buying decision. This study was conducted in Surabaya, the second biggest cities in Indonesia, where usually men are expected to have a good personal appearance. This research will use social expectation, and product sensorial as a dependent variable to influence the buying decision. From the result it can be conclude that even though the societies have an expectation for the men to perform good personal appearance, but the product sensorial still have dominant factor to influence the buying decision for man personal care products.Key Words- Product sensorial experience, Social expectation, buying decision